2019
DOI: 10.3892/ijmm.2019.4391
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin suppresses the migration and invasion of human liver cancer cells by downregulating the expression of CXCR4

Abstract: Liver cancer is a worldwide threat to human health. High expression levels of C-X-C chemokine receptor type 4 (CXCR4) have been reported to promote the migration and invasion capacities of liver cancer cells. Cordycepin, extracted from Cordyceps militaris, has anti-inflammatory, antioxidant and anticancerous properties. Therefore, in the present study, migration assays, western blotting, reverse transcription-quantitative PCR and immunofluorescence analyses were conducted to determine whether cordycepin was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…( 18 , 21 ) Cordycepin suppresses the migration and invasion of human liver cancer cells. ( 22 ) However, the protective effects of cordycepin against the progression of NASH and the underlying mechanisms of action of these effects remain unknown.…”
mentioning
confidence: 99%
“…( 18 , 21 ) Cordycepin suppresses the migration and invasion of human liver cancer cells. ( 22 ) However, the protective effects of cordycepin against the progression of NASH and the underlying mechanisms of action of these effects remain unknown.…”
mentioning
confidence: 99%
“…Results revealed a dose-dependent increase in migration, which was not linearly related to dose ( Figure 4 ). Previous authors have reported a reduction in migration of cancer cells in the presence of Cordycepin [ 15 , 16 ]. However, our study reports an increase in migration of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, behavioural activity after TFF2 injection with or without pre-infusion of CXCR4 is to be investigated as well [ 66 , 91 ]. Importantly, expression of CXCR4 in other tissues including digestive tract and metabolic tissues [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ], could suggest a metabolic action of TFF2 via CXCR4 within these tissues.…”
Section: Tff2 Metabolic Properties and Implicationsmentioning
confidence: 99%